The Case Against Race Profiling in Immigration Enforcement - Johnson, Kevin R. (2000)
Although focusing on race profiling in immigration enforcement, this Article analyzes issues that implicate civil rights concerns cutting to the core of equal citizenship and full membership for Latinos, and other minority groups, in the national community. Part II of this Article summarizes criticisms of race profiling in criminal law enforcement and analyzes the law that, although offering somewhat flawed remedies, prohibits exclusively race-based criminal law investigatory stops. Part III analyzes the impact on immigration law enforcement of the Supreme Court decisions permitting consideration of race to justify stopping an individual. Part IV sketches the civil rights implications of racially discriminatory immigration enforcement. This Article contends that the Supreme Court should prohibit the INS from using race profiling in immigration enforcement